Discovery of oxindole‐based FLT3 inhibitors as a promising therapeutic lead for acute myeloid leukemia carrying the oncogenic ITD mutation. Issue 2 (20th November 2022) - Bender, Onur; Shoman, Mai E.; Ali, Taha F. S.; Dogan, Rumeysa; Celik, Ismail; Mollica, Adriano; Hamed, Mohammed I. A.; Aly, Omar M.; Alamri, Abdulwahab; Alanazi, Jowaher; Ahemad, Nafees; Gan, Siew Hua; et al.
Abstract: FMS‐like tyrosine kinase 3 (FLT3) mutations occur in approximately 30% of acute myeloid leukemia (AML) patients. In the current study, the oxindole chemotype is employed as a structural motif for the design of new FLT3 inhibitors as potential hits for AML irradiation. Cell‐based screening was performed with 18 oxindole derivatives and 5a–c inhibited 68%–73% and 83%–91% of internal tandem duplication (ITD)‐mutated MV4‐11 cell growth for 48‐ and 72‐h treatments while only 0%–2% and 27%–39% in wild‐type THP‐1 cells. The most potent compound 5a inhibited MV4‐11 cells with IC50 of 4.3 µM at 72 h while it was 8.7 µM in THP‐1 cells, thus showing two‐fold selective inhibition against the oncogenic ITD mutation. The ability of 5a to modulate cell death was examined. High‐throughput protein profiling revealed low levels of the growth factors IGFBP‐2 and ‐4 with the blockage of various apoptotic inhibitors such as Survivin. p21 with cellular stress mechanisms was characterized by increased expression of HSP proteins along with TNF‐β. Mechanistically, compounds 5a and 5b inhibited FLT3 kinase with IC50 values of 2.49 and 1.45 µM, respectively. Theoretical docking studies supported the compounds' ability to bind to the FLT3 ATP binding site with the formation of highly stable complexes as evidenced by molecular dynamics simulations. The designed compounds also provide suitable drug candidates with no violation of drug likeability rules. Abstract : A series of oxindole compounds (5a–c and 6a–o ) carrying a vanillin functionality were designed and synthesized as FMS‐like tyrosine kinase 3 (FLT3) inhibitors for acute myeloid leukemia (AML). The oxindole compounds were more effective on MV4‐11 cells than on THP‐1 cells, demonstrating selective inhibition against the oncogenic internal tandem duplication (ITD) mutation. Compound 5a has the potential to become a specific therapeutic agent in ITD‐mutated AML.